Learning Management in New Normal Towards Sustainable Development - Jitchayawanit, Kulisara; Suwanasri , Nittaya; Khamkhad, Udom; krutmuang , Chalayut; Rojananiti, Sumitra (Journal of Modern Learning Development, 2022)
Derive from serious problems in Thai society and world societies of the past 1-3 years of the spread of Coronavirus (COVID-19), a lot of danger affected people’s lives in many dimensions. Jobs, health, daily-lives and educational management have changed. The most affected issues which were seen vividly was educational management. Institutions had to adapt or final alternative ways to develop learners. To solve the problems these concern the learners. They could not come to learn in school as usual. To fulfill the learners need of learners and guardians in new normal. All have to be opened mind to accept. For the learning in new normal for sustainable development the institution should develop learners in many learning, in order to develop a perfect human, seven knowledgeable, good, thoughtful, be Thai, technology skillful, modern and happy, learning though on site, on air, learning on demand, learning on-hand, learning on technology, on self-directed learning, and active learning.